Principal’s efforts to change in schools: A case study in Indonesia - Isnaini Isnaini; Melisa Melisa; Rusdinal Rusdinal; Nurhizrah Gistituati (Journal of Social, Humanity, and Education, 2021)
Purpose: This study aims at describing the principals’ efforts to make changes, the factors supporting the changes, and inhibiting factors. Research methodology: This research uses a literature review method to describe the principals’ efforts to make changes, the factors supporting the changes, and inhibiting factors. Results: The results show that (1) the principals’ efforts to make changes include catalysts, creators, facilitators, and stabilizers, (2) the supporting factors are the principals’ efforts to make changes and support from teachers and parents to make these changes, and (3) there are several factors, including inhibiting factors. These factors are unfolding needs which include economy, social needs, self-esteem, and individuals that requirefinding new work methods, new work groups that cause inconvenience and obscurity to achieve, limiting the individuals’ share of information and school organizational resources, and orthodox thinking leading to underdevelopment of knowledge and skills as well as limiting authority, increasing workload, increasing number of rules, and intimidating individual career development. Limitations: This study only focuses on the principle of making changes, the factors supporting the changes, and inhibiting factors. Contribution: This research contributes to the principals’ efforts to make changes, the factors supporting the changes, and inhibiting factors to achieve school goals and a good leader to manage the school.